Evaluating bio-safety of newer and conventional insecticides against parasitoids and predators of castor whitefly: Evaluating bio-safety of newer and conventional insecticides against parasitoids and predators of castor whitefly - M SENTHIL KUMAR; M DEIVAMANI; S R VENKATACHALAM (Journal of Oilseeds Research, 2020)
This investigation was carried out to evaluate the bio-safety of newer and conventional insecticides tested against Eretmocerus mundus, Nephus regularis, Chilocorus nigirita under laboratory conditions at Tapioca and Castor Research Station, Yethapur. The results showed that diafenthiuron 50 WP @ 0.8g/l and buprofezin 25 SC @ 0.8 ml/l recorded lowest adult mortality of Eretmocerus mundus (60 and 65 percent), Nephus regularis (40.60 and 39.40 per cent) and Chilocorus nigirita (39.20 and 34.60 per cent) respectively and highest adult emergence (74.41 and 73.49 percent) in Eretmocerus mundus. However, thiomethaxam 25 WG0.4 g/l and dimethoate 30 EC1.7 ml/l were very harmful to parasitoid and predators.